Estratégias para transmissão e recepção de streaming de vídeos em dispositivos móveis - Coriolano Filho, Fábio Sobreira (2010)
Streaming audio and video is a technology that can provide a data stream from a server, through the continuous burst of media packets, captured by a stand-alone player or plugin in a sufficient time to load continuous portions of the video screen, without interruption . The idea is that the server and player work together, causing the data to be transmitted in real time. This paper proposes techniques for transmission, reception, persistence and search streaming video on mobile platforms, using open source software and standards. These techniques were compared and pointed out advantages and disadvantages of each and the players on the market. There were also used standard specifications for 3GP and specialized protocols, which define access control and distribution of multimedia content.